Genetic variants in CYP2B6 and CYP2A6 explain interindividual variation in efavirenz plasma concentrations of HIV-infected children with diverse ethnic origin. - Sandra Soeria-Atmadja; Emma Österberg; Lars L Gustafsson; Marja-Liisa Dahl; Jaran Eriksen; Johanna Rubin; Lars Navér (PLoS ONE)
Background Approximately 2.6 million children live with HIV globally, and efavirenz (EFV) is one of the most widely used antiretroviral agents for HIV treatment in children and adults. There are concerns about the appropriateness of current EFV dosing and it has been discussed whether EFV dosing should be adapted according to genotype in children as suggested for adults. Aim To investigate if pediatric EFV dosing should be guided by genetic variation in drug metabolizing enzymes rather than by body weight. Method EFV plasma concentrations measured for clinical purposes from all children less than 18 years old at Karolinska University Hospital, Stockholm, Sweden, treated with EFV were collected retrospectively. They were genotyped for eleven polymorphisms in genes coding for drug-metabolizing enzymes and P-glycoprotein, of potential importance for EFV disposition. Data on country of origin, sex, age, weight, HIV RNA, viral resistance patterns, CD4 cells, adherence to treatment, subjective health status and adverse events were collected from their medical records. Results Thirty-six patients and 182 (mean 5 samples/patient) EFV plasma concentration measurements from children of African, Asian and Latin American origin were included. EFV plasma concentration varied 21-fold between measurements (n = 182) (0.85-19.3 mg/L) and 9-fold measured as mean EFV plasma concentration across the subjects (1.55-13.4 mg/L). A multivariate mixed-effects restricted maximum likelihood regression model, including multiple gene polymorphisms, identified CYP2B6*6 T/T (p < 0.0005), CYP2B6*11 G/G (p < 0.0005), CYP2A6*9 A/C (p = 0.001) genotypes, age at treatment initiation (p = 0.002) and time from treatment initiation (p < 0.0005) as independent factors significantly related to loge concentration/(dose/weight). The contribution of the model to the intra- and interindividual variation were 6 and 75%, respectively (Bryk/Raudenbush R-squared level). Conclusion Genetic polymorphisms in CYP2B6 and CYP2A6 explained a significant proportion of variability in EFV plasma concentration in HIV-infected children in a multi-ethnic outpatient clinic. Knowledge about individual variants in key drug metabolizing enzyme genes could improve clinical safety and genotype directed dosing could achieve more predictable EFV plasma concentrations in HIV-infected children.